If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -1)(x + 4)(2x + -3) = 0 Reorder the terms: 5(-1 + x)(x + 4)(2x + -3) = 0 Reorder the terms: 5(-1 + x)(4 + x)(2x + -3) = 0 Reorder the terms: 5(-1 + x)(4 + x)(-3 + 2x) = 0 Multiply (-1 + x) * (4 + x) 5(-1(4 + x) + x(4 + x))(-3 + 2x) = 0 5((4 * -1 + x * -1) + x(4 + x))(-3 + 2x) = 0 5((-4 + -1x) + x(4 + x))(-3 + 2x) = 0 5(-4 + -1x + (4 * x + x * x))(-3 + 2x) = 0 5(-4 + -1x + (4x + x2))(-3 + 2x) = 0 Combine like terms: -1x + 4x = 3x 5(-4 + 3x + x2)(-3 + 2x) = 0 Multiply (-4 + 3x + x2) * (-3 + 2x) 5(-4(-3 + 2x) + 3x * (-3 + 2x) + x2(-3 + 2x)) = 0 5((-3 * -4 + 2x * -4) + 3x * (-3 + 2x) + x2(-3 + 2x)) = 0 5((12 + -8x) + 3x * (-3 + 2x) + x2(-3 + 2x)) = 0 5(12 + -8x + (-3 * 3x + 2x * 3x) + x2(-3 + 2x)) = 0 5(12 + -8x + (-9x + 6x2) + x2(-3 + 2x)) = 0 5(12 + -8x + -9x + 6x2 + (-3 * x2 + 2x * x2)) = 0 5(12 + -8x + -9x + 6x2 + (-3x2 + 2x3)) = 0 Combine like terms: -8x + -9x = -17x 5(12 + -17x + 6x2 + -3x2 + 2x3) = 0 Combine like terms: 6x2 + -3x2 = 3x2 5(12 + -17x + 3x2 + 2x3) = 0 (12 * 5 + -17x * 5 + 3x2 * 5 + 2x3 * 5) = 0 (60 + -85x + 15x2 + 10x3) = 0 Solving 60 + -85x + 15x2 + 10x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5'. 5(12 + -17x + 3x2 + 2x3) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(12 + -17x + 3x2 + 2x3)' equal to zero and attempt to solve: Simplifying 12 + -17x + 3x2 + 2x3 = 0 Solving 12 + -17x + 3x2 + 2x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -2=-1.75k | | 25=5(9x-4) | | 2x-9=6x-13 | | -2(3)+5+5(3)= | | 6x-2=12x+1 | | 2x^3-3x-20=0 | | y-(-16)=-12 | | -18+30=-4(x+5) | | x+(-24)=-38 | | -4(x+3)=4 | | 1x/19=20 | | .42*n=.6 | | 8-5x-6-9x=4 | | x(2x+5)=0 | | 6x+3=6x+2x-21 | | -14=-3x-65 | | -9(x+3)-(1+4x)=-14x | | f(-2)=1+5(-2) | | 198=(x+11)(x) | | x+2=3(2x-6) | | 6k-24=7-2k | | 3t=3t-21 | | 2(2x-5)=3(x+2) | | -7+n=8 | | 6r-4-2r=8r-4 | | 1-5x=-39 | | 4x+73yv=568x | | 80=x(x-3)2 | | 19.4=x+2 | | -7x+21=-4 | | s=35+0.3s | | -16-5x=24+3x |